Carbon stored in aerial biomass and its economic valuation in the agroforestry systems of the EEA San Bernardo, Madre de Dios - Peru - Clemente-Arenas, Edith R. (2022)
Agroforestry systems are a sustainable management alternative for land degraded by conventional agriculture in the Peruvian Amazon, this could prevent further deforestation of forests and the loss of more ecosystems. The tree component in agroforestry systems makes them more similar to natural forests than many other land use systems such as pastures, monocultures, among others. This characteristic also affects the carbon sequestration potential of agroforestry systems, since they represent a considerable carbon sink both above and below ground. Consequently, it can represent a considerable economic income from carbon credits, which is an international decontamination mechanism to reduce polluting emissions to the environment, with a relatively new market and with great relevance in mitigating climate change. In this sense, the carbon stored in the aerial biomass of seven agroforestry systems established more than 16 years ago at the San Bernardo Agricultural Experimental Station (EEA) was quantified and economically valued. The diameter of fruit and forest species was used as input for the allometric equations that allowed us to estimate biomass and carbon stored in the tree component of agroforestry systems. The seven agroforestry systems of the EEA San Bernardo have a total of 483.81 Mg of carbon stored in their aerial biomass. This amount of carbon represents USD $13,353.16 in carbon credits for the 2020 price. Brazil nut (Bertholletia excelsa Bonpl.) was the species with the highest amount of carbon stored among the seven agroforestry systems, while pashaco (Schizolobium amazonicum Huber ex Ducke) showed considerable carbon storage despite being only five years old. Our results show that some combinations of forest and fruit species generate interspecific competition that favors SAF, making it more productive in terms of growth and carbon storage.